Farm restructuring in Uzbekistan: What next? - Martin Petrick; Nodir Djanibekov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2019)
After two and a half decades of state-mandated cotton production, the diversification of agriculture and the downsizing of the cotton area have become prominent features of Uzbekistan's current modernization strategy. Given the momentum of agricultural policy reform, this policy brief aims to evaluate the success of farm restructuring so far. Moreover, it asks what policymakers should do next to promote agricultural competitiveness without losing sight of the social consequences of reform. After initial downsizing of the former collective farms and achieving nominal self-sufficiency in grain during the 1990s, the government has struggled to find a new model for its farming sector. In January 2019, the government initiated a new wave of farm consolidation. Rather than targeting at a particular type or size of farm organization, policymakers are recommended to focus instead on ensuring that all farmers receive undistorted market signals and have access to an optimal set of supporting public services. Stepwise liberalization of output and factor markets will contribute to this goal, and it needs to be complemented by better tailored public services to Uzbekistan's heterogeneous farming sector to lead to a successful agricultural transformation. The latter is especially important for household producers who will likely appreciate better non-farm income opportunities generated by reforms that go beyond the agricultural sector.
urn:nbn:de:gbv:3:2-107420
Keywords: 330